2017
DOI: 10.1016/j.jembe.2016.10.031
|View full text |Cite
|
Sign up to set email alerts
|

Impact of food type on respiration, fractionation and turnover of carbon and nitrogen stable isotopes in the marine amphipod Gammarus aequicauda (Martynov, 1931)

Abstract: This study experimentally determined the impact of food source type on turnover rate and trophic enrichment factors (TEFs or Δ) of δ 13 C and δ 15 N, as well as on respiration rate, in captive populations of the marine amphipod Gammarus aequicauda. Gammarus aequicauda (318 individuals) were fed ad libitum with three food sources animal, algae, and dead Posidonia oceanica leaves (also called "litter"), varying in palatability, digestibility, nutritional qualities and isotopic compositions, for between four and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 80 publications
0
15
0
Order By: Relevance
“…New and previously published data showed that G. aequicauda, which is often described as a herbivore and detritivore (Cummins & Klug, 1979;Graca et al, 2001), intensively consumes different animals, which are an essential part of its diet (Remy, Darchambeau, Melchior, & Lepoint, 2017;Shadrin et al, 2019). Vladimir Yakovenko http://orcid.org/0000-0001-8926-0180 Elena Anufriieva http://orcid.org/0000-0002-6237-7941…”
Section: Discussionmentioning
confidence: 99%
“…New and previously published data showed that G. aequicauda, which is often described as a herbivore and detritivore (Cummins & Klug, 1979;Graca et al, 2001), intensively consumes different animals, which are an essential part of its diet (Remy, Darchambeau, Melchior, & Lepoint, 2017;Shadrin et al, 2019). Vladimir Yakovenko http://orcid.org/0000-0001-8926-0180 Elena Anufriieva http://orcid.org/0000-0002-6237-7941…”
Section: Discussionmentioning
confidence: 99%
“…The key results presented in the present paper do not seem to depend on methodological bias. The individual metabolic rates of aquatic organisms are assessed in the literature by various methods including flow through (Vignes et al, 2012), closed system (Toman and Dall, 1998;Remy et al, 2017) and intermittent flow (Svendsen et al, 2016). The latter two methods have been shown to be more sensitive than the former to oxygen stress and accumulation of individual excretion products (Franke, 1977;Gnaiger, 1983;Lampert, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Lekanesphaera monodi (Vignes et al, 2012); and (v) resource quality, with a direct response of standard metabolic rates to increasing resource quality, e.g. Gammarus aequicauda fed on live prey or Flabellia petiolata or P. oceanica leaves (Remy et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…These values contrast with widely-used values from previous meta-analysis 56 that present averages from 61 different species of aquatic and terrestrial vertebrates and invertebrates in a variety of taxa: arthropods, molluscs, nematodes, birds, fish and mammals (for information, values in 56 were 0.5 ± 0.13‰ for δ 13 C and 2.3 ± 0.18‰ for δ 15 N). Nevertheless, we chose the mantis shrimp values 54 , firstly, on the basis that these fractionation values were calculated from a decapod crustacean: taxonomic relatedness is important due to evidence that TEFs are taxon-specific due to shared physiological processes at taxon level [57][58][59][60][61] . Secondly, the values in 54 represented lipid-corrected stable isotope ratios for consumers and prey, as also used in our study, and were from a diet shift controlled laboratory experiment.…”
Section: Data Analysis the Package Simmr -Stable Isotopesmentioning
confidence: 99%